Aqui é trabalho: documentário sobre a produção de conteúdo e gestão das redes sociais do candidato Romero Rodrigues - Campina Grande - 2016 - Saraiva, Emerson José Pereira (2017)
Based on the importance of Online Social Networks in the process of debate and construction of the Brazilian political-electoral scenario, the present academic work provided the realization of an audiovisual documentary with the objective of demonstrating how the process of content production and Management of communication in digital & online media during the electoral campaign of the candidate Romero Rodrigues (PSDB), in Campina Grande, Paraíba, in the year 2016. For this, were analysed the main pieces of political-electoral propaganda produced by the digital marketing coordination of the campaign, as well as the dynamics of the teams involved in the creation, production, dissemination and relationship processes. From the methodological point of view, the product was constructed from a bibliographical research on Political Propaganda, Electoral Marketing and Content Production for Social Networks and through the use of exploratory research techniques, combined with participant observation. The reports and pieces were presented in the form of a full length documentary, capable of demonstrating the complexity of the work performed and its participation in the final result of the campaign.